2019
DOI: 10.1108/sej-02-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Action research and participatory democracy in social enterprise

Abstract: Purpose The purpose of this paper is to introduce the reader to the Nordic tradition of Critical Utopian Action Research (CUAR) and to demonstrate how CUAR might reinvigorate participatory democracy as an intrinsic characteristic of social enterprise. This leads us to sketch out the beginnings of how researchers might work with communities to help realise their democratic impulses through social enterprise. Design/methodology/approach This paper aims to synthesise the participatory action research literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Finally, even though democratic (participatory) decision-making is a normatively expected feature of SEs (European Commission, 2019), it is associated with significant challenges and tensions according to our results and those of others. Social entrepreneurs often feel that both social and business goals may be more immediately served through hierarchical decision-making structures (Gleerup et al, 2019). Similar arguments can be found against public participation in the literature on participatory decision-making (Bajm ocy and G ebert, 2014), even though, according to most scholars, the advantages of participatory democratic decision-making clearly outweigh the costs.…”
Section: Tensions Related To Organizational Operationsmentioning
confidence: 79%
See 1 more Smart Citation
“…Finally, even though democratic (participatory) decision-making is a normatively expected feature of SEs (European Commission, 2019), it is associated with significant challenges and tensions according to our results and those of others. Social entrepreneurs often feel that both social and business goals may be more immediately served through hierarchical decision-making structures (Gleerup et al, 2019). Similar arguments can be found against public participation in the literature on participatory decision-making (Bajm ocy and G ebert, 2014), even though, according to most scholars, the advantages of participatory democratic decision-making clearly outweigh the costs.…”
Section: Tensions Related To Organizational Operationsmentioning
confidence: 79%
“…Family atmosphere SEs focus on the social well-being of employees, as reflected in how the organization is governed, which is associated with potential costs -Democratic decision-making Democratic decision-making should be a characteristic of SEs (normative requirement) Nyssens, 2010a, 2010b) Tension related to democratic (participatory) decisionmaking) (Gleerup et al, 2019) Source: Authors' construction Table 6.…”
Section: ) Dependency Vs Independencementioning
confidence: 99%
“…It has been suggested that more democratically managed organizations can make a significant contribution to enhancing, facilitating and promoting the co-production of public services between citizens and the government (Pestoff, 2012). As a consequence, it contributes to promote more democratic societies (Defourny & Nyssens, 2010;Gleerup et al, 2019;Pestoff & Hulgard, 2016).…”
Section: Participatory Managementmentioning
confidence: 99%
“…109–110). Gleerup et al (2019) propose that rather than living up to their potential as “‘schools of democratic participation and active citizenship’ (Prodi, 2002)” (Gleerup et al , 2019, p. 46), SE is often presented as merely “a technical solution to the problems of the state or market (Dey and Steyaert, 2012)” (Gleerup et al , 2019, p. 55). This conversation seems to point out that community-based SEs are alternative forms of organizing, founded on different principles than market capitalism (Finlayson and Roy, 2019, p. 79), and that its practice and research hold a radical intent.…”
Section: Introductionmentioning
confidence: 99%
“…Given that SE is sometimes presented as an already charted terrain, known, plan-able (e.g. Spreckley, 2011) and subject to the rules of management (Dey and Steyaert, 2012, p. 91), exploring the less charted landscape outside of the bounded and controlled terrain of mainstream management theories might open up imaginative possibilities and, as I will argue later on, reconnect it to its democratizing intent (Gleerup et al , 2019).…”
Section: Introductionmentioning
confidence: 99%